Psychiatric manifestations of Lyme disease - Padała, Olga; Krupa, Adrianna; Putowski, Maciej; Konopelko, Michał; Piasek, Ewa (Journal of Education, Health and Sport, 2019)
Introduction: Lyme disease is an infectious disease caused by Borrelia bacteria. Characteristic symptoms are erythema migrans, facial nerve palsy, aseptic meningitis, acquired heart blocks, chronic arthritis and radiculitis. The psychiatric manifestations of Lyme disease are known. They include cognitive, emotional and behavioral symptoms and syndromes. Purpose: The aim of the review was to present psychiatric disorders caused by Borrelia infection. State of knowledge: There are three basic types of infections causing neuropsychiatric symptoms: the meningovascular form associated with cerebrovascular infarcts; infection within the central nervous system which is the atrophic form of Lyme meningoencephalitis and is associated with cortical atrophy, gliosis and dementia and the last is infection outside the CNS causing immune and other effects within the CNS that contribute to neuropsychiatric symptoms. A range of psychiatric manifestations of borreliosis include psychosis, sleep disorders, anxiety disorders, depression, obsessive-compulsive disorder, intrusive symptoms, cognitive impairments and rapidly developing dementia. Summary: Lyme disease is a common problem in medical practice of many health professionals. It is important that physicians of different specialties, including psychiatrists, consider Lyme disease in differential diagnosis. Appropriate pharmacotherapy can stop the progression of the disease and improve the patient’s quality of life.